If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(2x + -7) = 7 + 6x Reorder the terms: 7(-7 + 2x) = 7 + 6x (-7 * 7 + 2x * 7) = 7 + 6x (-49 + 14x) = 7 + 6x Solving -49 + 14x = 7 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -49 + 14x + -6x = 7 + 6x + -6x Combine like terms: 14x + -6x = 8x -49 + 8x = 7 + 6x + -6x Combine like terms: 6x + -6x = 0 -49 + 8x = 7 + 0 -49 + 8x = 7 Add '49' to each side of the equation. -49 + 49 + 8x = 7 + 49 Combine like terms: -49 + 49 = 0 0 + 8x = 7 + 49 8x = 7 + 49 Combine like terms: 7 + 49 = 56 8x = 56 Divide each side by '8'. x = 7 Simplifying x = 7
| 3x^2-1x-24=0 | | 3/5g-1/3=-31/3 | | 6x+30=.5(12x+60) | | 10u+7u-5u-3u=18 | | 3y/5=15 | | 14p-3p-6p=10 | | 4+2.3h=-3.7 | | 7u+8u-9u-3u=20 | | 150=6(-6x-5) | | 2-b/3=-21/2 | | 7(y-1)=-7-4y | | 10x-9=-9+10 | | 8pq+6pr-4ps= | | 1/6q-4=-1 | | 1-2x=7-4x | | 3+(4-x)=6x | | 3(X+4)=-2x-x+12 | | 150=6(6x-5) | | 14b+16b-3=9 | | 8-(7y+5)=3[(4y-5)-(y-2)] | | 7-2x=8-x | | 4x+7=3x+17 | | 7x=-60+4 | | 10b-6b+3b-7b+b=13 | | 5v^2+25+30= | | t/-3=-1-5 | | 7y+7y+21=-21 | | 3(2t-4)+10=4(t-1)-(3t+1) | | 1.5(4x+6)=.66(9x-24) | | 19q+2q+-6=11 | | t/3=-1-5 | | 4d+2d+4d-9d=17 |